KOMPETENSI GURU DALAM MENANAMKAN NILAI-NILAI AKHLAK MULIA DALAM PEMBELAJARAN PAI DI SEKOLAH - MISBAHUDDIN, MISBAHUDDIN (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2017)
This research is an explanation which shows that Islamic Education (PAI) teacher must have competenced such as pedagogic, social, personality, propesionalisme, in carrying out the learning process of PAI teacher, before implementing learning firstly arrange the lesson plan, and evaluate it. The Cultivation of Moral Value conducted by the teacher of PAI, doing the study of the Qur'an, pesantren kilat, and social service. Supporting and inhibiting factors are teachers, curriculum, parent participation, family environment, community environment, and the flow of modern globalization. The solution of parent's cooperation with teachers in instilling the values of good and / or honorable both in school and family and anticipate the association in public life. The implications of this research are: 1) The general teachers and teachers of PAI in particular, to further improve the competence and methods in learning, 2) The efforts that have been done by PAI Teacher in instilling the values of the noble character of the learners who are deemed to be effective are worthy to be maintained and developed. 3) The obstacles faced in the effort to cultivate the values of morals in the students must always diminimasir always evaluate, with improving learning facilities, establish cooperation and active communication between teachers, local government and local communities.